2022
DOI: 10.3390/nano12111813
|View full text |Cite
|
Sign up to set email alerts
|

Waterproof and Moisture-Permeable Polyurethane Nanofiber Membrane with High Strength, Launderability, and Durable Antimicrobial Properties

Abstract: Nanofiber membrane has high biological protection function because of its good waterproof and moisture permeability properties. However, this membrane usually lacks active antimicrobial properties, limiting the application in reusable bioprotective textiles. Herein, waterborne polyurethane-capped Ag nanoparticles (AgNPs) were synthesized by reducing silver nitrate in water by sodium borohydride in the presence of polyurethane. AgNP-embedded thermoplastic urethane (TPU) nanofiber membrane was prepared by electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…While this test method, also known as the cup test [ 159 ], is most often used to investigate the water vapor permeability of electrospun nanofiber mats, it is nevertheless not free of potential errors. As Mustapha et al discussed, the measured water vapor permeability actually consists of three different resistances: those of the air cavity over the water, then the actual intrinsic membrane resistance, and finally the boundary air layer resistance, the latter of which the authors suggested to reduce by introducing a fan blowing the air above the cups away, while they used an open control cup to measure the air resistance by comparing the evaporation from this cup with an analytical model [ 160 ].…”
Section: Water Vapor Permeabilitymentioning
confidence: 99%
“…While this test method, also known as the cup test [ 159 ], is most often used to investigate the water vapor permeability of electrospun nanofiber mats, it is nevertheless not free of potential errors. As Mustapha et al discussed, the measured water vapor permeability actually consists of three different resistances: those of the air cavity over the water, then the actual intrinsic membrane resistance, and finally the boundary air layer resistance, the latter of which the authors suggested to reduce by introducing a fan blowing the air above the cups away, while they used an open control cup to measure the air resistance by comparing the evaporation from this cup with an analytical model [ 160 ].…”
Section: Water Vapor Permeabilitymentioning
confidence: 99%
“…The process of tailoring has been obtained by the process of requirement for several applications. Recently, several researchers worked on transition metallic elements such as Ti [26,27], Cr [28], W [29,30], Mn [31], Fe [32][33][34] Co [35][36][37], Ni [38], Pt [39], Cu [40], Ag [41,42], and Au [43]. The copper transition metal is low-cost materials and it is ideal for physical and chemical preparation techniques compared to transition metals viz., Ti, Cr, W, Pt, Ag, and Au.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning technology is a low-cost and high-efficiency method for preparing nanofiber membranes. More and more polymers are electrospun into nanofibers, such as polyacrylonitrile (PAN), polyurethane (PU), polyvinylpyrrolidone (PVP), poly­(vinylidene fluoride) (PVDF), poly­(vinyl alcohol) (PVA), etc. The obtained polymer nanofiber membrane has the characteristics of nanoscale fiber diameter, high porosity, small pore size, and adjustable pore structure, so it is widely used as waterproof and breathable medical or filtration materials. For these applications, outstanding hydrophobicity is often a precondition or very necessary. At present, the normal way of preparing hydrophobic materials is to reduce the surface energy or increase the surface roughness of materials. Some studies have shown that the introduction of inorganic nanoparticles on the material surface can not only reduce the surface energy of the material but also improve the surface roughness of the material …”
Section: Introductionmentioning
confidence: 99%